Gross National Happiness in Brazil: An analysis of its determinants - Lilian Lopes Ribeiro; Emerson Luis Lemos Marinho (EconomiA, 2017)
It analyzed the determinants of happiness in Brazil from two categories of variables, formed by micro variables and other macros by socioeconomic variables. Considering the basis of data from WVS and IPEA for the years 2006 and 2014, estimated a logit model ordered and their marginal effects. Among the results, it was concluded that income positively influences the probability of being happy and that the Easterlin paradox remains also in Brazil. Since income is not the only determinant of influence on the probability of happiness, suggests the creation of an index with additional factors to measure well-being. – – Analisa-se os determinantes da felicidade no Brasil a partir de duas categorias de variáveis, uma formada por variáveis micros e outra por variáveis macros socioeconômico. Considerando a base nos dados da WVS e do IPEA para os anos de 2006 e 2014, estimou-se um modelo logit ordenado e seus efeitos marginais. Dentre os resultados, concluiu-se que a renda influencia positivamente a probabilidade de ser feliz e que o paradoxo de Easterlin se mantém também no Brasil. Desde que a renda n\~ao é o único determinante de influência sobre a probabilidade de felicidade, sugere-se a criaç\~ao de um índice com fatores adicionais para mensurar o bem-estar."
Keywords: 330; Happiness; Gross National Happiness; Welfare; felicidade; felicidade interna bruta; bem-estar